Experimental Research on the Specific Energy Consumption of Rock Breakage Using Different Waterjet-Assisted Cutting Heads - Hongxiang Jiang; Deguang Meng (Advances in Materials Science and Engineering)
To investigate the specific energy consumption (SE) of rock breakage by cutting heads assisted by different types of waterjet and to identify optimal waterjet parameters and assistance types, rock cutting with and without waterjets was carried on a rock fragmentation test bed. SE is a comprehensive evaluation index and was developed according to the applied load on cutting head, and the SE under different cutting conditions was compared and analyzed. The results show that the SE of rock breakage without waterjet assistance increased with the increasing of rock compressive strength (RCS) but that the limited drilling depth decreased. The effect of the waterjet pressure on the SE of rock breakage by the cutting head I was marked, and SE decreased by 30∼40% when the ratio between RCS and waterjet pressure was less than 1. However, the function of the waterjet assistance was poor; therefore, a ratio of 1 could be used to distinguish the rock breakage effect of cutting head I. For cutting head II, the rock damage from the waterjet impact was limited due to the large waterjet standoff distance; thus the rock breakage performance of cutting head II was also limited. The waterjet impacting at the tip of the conical pick using cutting head III could enter into the cracks caused by the mechanical pick and fracture the rock. Therefore, the rock breakage performance of cutting head III was better than that of cutting head II.